Determination of engineering properties of market ssamples of khoa-peda for its application in process mechanization - Singh, Gursharn (Indian Journal of Dairy Science, 2018)
Samples of different varieties khoa-peda from the local market in the Karnal city of Haryana, were analyzed with regard to their composition, geometrical and physical attributes and textural properties to provide the basis for process mechanization of khoa-peda production technology. The thickness of peda varied between 1.807±0.11 to 2.330±0.03 cm, diameter 2.983±0.09 to 4.160±0.05 cm, weight 13.460±0.08 to 26.047±0.13 g and density 1.020±0.08 to 1.130±0.10 g /cm3.  Among the geometric property analysis, the geometric mean diameter (GMD) of different types of peda was found to be varying between 2.982±0.113 to 4.159±0.041 cm, sphericity 0.933±0.013 to 0.982±0.016 and the roundness of peda varied from 0.914±0.106 to 0.963±0.063. Khoa-peda with no added ingredient is more like a disc shape and has larger geometric mean diameter. The peda with added ingredients has higher sphericity and looks like a spheroid shaped. Also the corners of almost all types of peda are smoothened. The peda having ingredients in it were found to have lower density, whereas, the plain peda having no added ingredients had the highest density.The composition of market samples of khoa-peda was determined as: Fat 8.072±0.19% to 20.287±0.32% and Moisture content (w.b.) 12.790±0.11 to 22.900±0.23 %. Analysis of textural properties of khoa-peda revealed that there was a wide variation in its hardness that varied from 5.91 to 19.17 N, adhesiveness -0.19 to 0 N, springiness 0.04 to 0.08 mm, cohesiveness 0.05 to 0.09, gumminess 0.29 to 1.35 Nmm, chewiness 0.01 to 0.11 Nmm and resilience 0.02 to 0.03. For process mechanization of khoa peda formation, the composition of the raw material in terms of moisture content and fat content are important in deciding the process parameters of the peda formation, such as, temperature, pressure and design of extrusion die.